Adult duodenojejunal intussusception due to heterotopic pancreas - a rare entity (Bangladesh Journal of Medical Science, 2014)
Approximately 95% of intussusception occurs in children, However it is a rare entity in adults accounting for 0.003% to 0.02 % of all the hospital admissions. Various causes of intussusception are well known, However intussusception caused by heterotropic pancreas is extremely rare and the rarity increases manifolds if it is in the duodenum of an adult and the cause being heterotropic pancreas. We report this rare case of intussusception due to pancreatic heterotropia in 43 year old male who presented with acute pain abdomen. DOI: http://dx.doi.org/10.3329/bjms.v13i3.12781 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.340-342